Cu / ZrO2-coated NC catalyst for catalyzing ethanol to synthesize high alcohol as well as preparation method and application of Cu / ZrO2-coated NC catalyst

Through the preparation and application of Cu/ZrO2@NC catalyst, the problem of more by-product gases and low selectivity of C6+ products in ethanol synthesis is solved, and the high selectivity of C6+ high carbon alcohol is achieved, which improves the conversion rate of ethanol And break the traditional carbon chain distribution, with simple preparation and high reaction activity.

CN119303610AActive Publication Date: 2025-01-14GUANGDONG UNIV OF TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411412901.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the prior art, ethanol synthesis of high-carbon alcohols has problems such as a lot of by-product gases, low selectivity of C6+ products, and low ethanol conversion efficiency, making it difficult to achieve continuous synthesis and expansion of the carbon number range of high-carbon alcohols.

Method used

The catalyst is constructed by the sol-gel method to promote the uniform dispersion of copper on the zirconium oxide support, and carbon and nitrogen are introduced, combining aldehyde ketone coupling and Guerbet coupling reaction steps to achieve continuous catalysis of ethanol. Convert to C6+ high carbon alcohol and use appropriate metal matching ratio to promote carbon chain growth.

Benefits of technology

It achieves high selectivity to obtain C6+ high carbon alcohol, improves the ethanol conversion rate, breaks the traditional carbon chain distribution, and has the advantages of simple preparation, low cost, high reaction activity and excellent catalytic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303610A_ABST
    Figure CN119303610A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu / ZrO2-coated NC catalyst for catalyzing ethanol to synthesize high alcohol as well as a preparation method and application of the Cu / ZrO2-coated NC catalyst, and relates to the technical field of synthesis of high alcohol compounds. The preparation method comprises the following steps: adding copper salt, zirconium salt and polyacrylamide into water, dissolving and mixing, heating and stirring to form a complex homogeneous solution, and drying to obtain a copper-zirconium catalyst precursor; calcining the copper-zirconium catalyst precursor in an inert gas atmosphere to obtain a Cu / ZrO2-coated NC catalyst; the Cu / ZrO2-coated NC catalyst prepared by the invention has the characteristics of high load, low particle size and high directional reaction activity for high alcohols; when the catalyst is used for synthesizing high alcohol from ethanol, effective coupling of aldehyde ketone condensation and aldol condensation can be effectively realized, and an oil-phase product mainly containing C6 + high alcohol can be obtained with high selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol. The invention also relates to a preparation method and application of the catalyst. Background Art

[0002] As energy independence and sustainability issues become increasingly prominent, the development and production of renewable fuels and fine chemicals have received widespread attention. C6+ high-carbon alcohols have the advantages of high energy density, low corrosiveness, and low water absorption, and are one of the ideal substitutes for diesel blended fuels. However, the synthesis of high-carbon alcohols from ethanol is mainly carried out by Guerbet coupling in an intermittent reactor to synthesize high-carbon alcohols in an aqueous phase. There are problems such as difficulty in continuous synthesis, low carbon number range of synthesized high-carbon alcohols, and a large number of by-product gases. Therefore, it is urgent to study a method for preparing high-carbon alcohols from ethanol to improve the ethanol conversion rate and promote the carbon chain growth of high-carbon alcohols. Summary of the invention

[0003] In view of the above technical problems, the present invention provides a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol; the catalyst effectively solves the defects and shortcomings of the process of synthesizing higher carbon alcohols from ethanol, such as a large amount of by-product gas, low selectivity of C6+ products, and low ethanol conversion efficiency.

[0004] Another object of the present invention is to provide a method for preparing a Cu / ZrO2@NC composite catalyst.

[0005] The last object of the present invention is to provide a method for synthesizing higher carbon alcohols from ethanol using the Cu / ZrO2@NC composite catalyst. The method provided by the present invention can obtain an oil phase product mainly composed of C6+ higher carbon alcohols with high selectivity.

[0006] To this end, the first technical solution provided by the present invention is as follows:

[0007] A method for preparing a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol comprises the following steps in sequence:

[0008] 1) adding copper salt, zirconium salt and polyacrylamide into water to dissolve and mix, heating and stirring to form a complex homogeneous solution, and drying to obtain a copper-zirconium catalyst precursor;

[0009] 2) calcining the copper-zirconium catalyst precursor prepared in step 1) under an inert gas atmosphere to obtain a Cu / ZrO2@NC catalyst;

[0010] The molar ratio of the copper ions in the copper salt, the copper ions in the zirconium salt and the carbon of the polyacrylamide is (0.1-0.5):1:(0.5-2).

[0011] Furthermore, in the preparation method of the above-mentioned Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol, the copper salt is one or more of copper nitrate, copper chloride and copper acetate.

[0012] Furthermore, in the preparation method of the above-mentioned Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol, the zirconium salt is one or more of zirconium nitrate, zirconium citrate and zirconium hydroxide.

[0013] Furthermore, in the preparation method of the above-mentioned Cu / ZrO2@NC catalyst for catalyzing the synthesis of high-carbon alcohols from ethanol, the calcination parameters are: heating rate 5°C / min, temperature 500-600°C, and time 3h.

[0014] The present invention provides a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol, which is prepared by the preparation method described in the first technical solution.

[0015] The present invention also has a technical solution to provide the above-mentioned Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol for use in catalyzing the synthesis of higher carbon alcohols from ethanol.

[0016] The present invention also provides a method for synthesizing higher alcohols from ethanol, which comprises the following steps in sequence:

[0017] 1) 1 ml Cu / ZrO2@NC catalyst and 2 ml quartz sand were loaded into a fixed bed reactor and mixed evenly; the temperature was raised from room temperature to 400 °C at a rate of 5 °C / min under a hydrogen atmosphere and kept at this temperature for 2400 h. -1 Hydrogen gas space velocity 0.1MPa reduction for 2h;

[0018] 2) Keeping the H2 gas atmosphere unchanged, the pressure was increased to 2.5Mpa, the reaction temperature was 310℃, and the reaction time was 0.6h. -1 Anhydrous ethanol was added to the reactor at a liquid rate of 3600 h. -1 , reaction time 12h;

[0019] 3) Collect the generated gas and perform detection and analysis by FID-TCD gas analysis spectrum. Meanwhile, centrifuge and separate the liquid phase products, take the upper organic phase and the lower aqueous phase after standing, and perform detection and analysis by gas chromatography.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects:

[0021] The present invention comprehensively considers the synthesis method of synthesizing high-carbon alcohols through elementary reaction steps such as aldehyde-ketone coupling and Guerbet coupling, constructs a Cu / ZrO2@NC catalyst through a sol-gel method, promotes the uniform dispersion of Cu on a ZrO2 oxide carrier, and simultaneously dopes carbon and nitrogen to introduce a base center, promotes ethanol to continuously catalyze and convert ethanol to generate C6+ high-carbon alcohols through aldol condensation and aldehyde-ketone condensation, and at the same time, the appropriate ratio of copper and zirconium metals can effectively promote carbon chain growth and break the traditional carbon chain distribution. The synthesis method provided by the present invention has the advantages of simple preparation, low cost, high load, low particle size, excellent catalytic efficiency, high reaction activity, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the XRD pattern of the Cu / ZrO2@NC catalyst used in the synthesis method of the present invention.

[0023] Figure 2 TEM image of the Cu / ZrO2@NC catalyst used in the synthesis method of the present invention. DETAILED DESCRIPTION

[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0025] The C6+ higher alcohols described in the present invention refer to the total amount of higher alcohols having a carbon number of 6 or more (including 6).

[0026] The raw materials used in the present invention are all purchased from the market.

[0027] Example 1

[0028] (1) Preparation of Cu / ZrO2@NC catalyst:

[0029] 10.02g zirconium nitrate and 1.689g copper nitrate were dissolved in distilled water to prepare a 0.1M copper zirconium metal salt solution; 1.66g polyacrylamide was added to the copper zirconium metal salt solution; the copper zirconium metal salt solution with polyacrylamide was stirred at 80°C for 2 hours to uniformly mix to form a complex homogeneous solution, and then dried at 105°C for 12 hours to fully dry the sample; the sample was then placed in a tubular furnace in an inert gas atmosphere and heated to 550°C at 5°C / min, and calcined for 3 hours to obtain a Cu / ZrO2@NC catalyst;

[0030] Figure 1 This is the XRD pattern of the Cu / ZrO2@NC catalyst prepared in Example 1 of the present invention. Figure 2 TEM schematic diagram of the Cu / ZrO2@NC catalyst used in the synthesis method of the present invention. Figure 1 , Figure 2 It can be seen that Cu is evenly dispersed on the ZrO2 support.

[0031] Embodiment 2-8

[0032] Example 2-8 A method for preparing a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher alcohols from ethanol, the steps are the same as those in Example 1, and the differences are shown in Table 1. The parameter variables in Table 1 refer to the parameter changes in step (1).

[0033] Table 1. Reaction parameters of the synthesis method of Examples 1-8

[0034] Calcination temperature (℃) Zirconium: Carbon (molar ratio) Copper:Zirconium (molar ratio) Example 1 550 1:1 0.3:1 Example 2 500 1:1 0.3:1 Example 3 600 1:1 0.3:1 Example 4 550 0.5:1 0.3:1 Example 5 550 0.8:1 0.3:1 Example 6 550 2:1 0.3:1 Example 7 550 1:1 0.1:1 Example 8 550 1:1 0.5:1

[0035] Note: The carbon in the above table refers to the carbon in polyacrylamide.

[0036] Comparative Example 1

[0037] The steps are the same as those in Example 1, except that the molar ratio of carbon to zirconium in step (1) is 0:1.

[0038] Comparative Example 2

[0039] The steps are the same as those in Example 1, except that the molar ratio of copper to zirconium in step (1) is 0:1.

[0040] Application Example 1

[0041] 1 ml of Cu / ZrO2@NC catalyst was loaded into a fixed bed reactor, and 2 ml of quartz sand was mixed in to maintain a certain catalyst bed layer. The temperature was raised from room temperature to 400 °C at a rate of 5 °C / min in a hydrogen atmosphere and then kept at 400 °C for 2400 h. -1 Hydrogen gas space velocity 0.1MPa reduction for 2h;

[0042] (2) Keeping the H2 gas atmosphere unchanged, the pressure was increased to 2.5 MPa, the reaction temperature was 310°C, and the reaction time was 0.6 h. -1 Anhydrous ethanol was added to the reactor at a liquid rate of 3600 h. -1 , react for 12h.

[0043] (3) The generated gas was collected and analyzed by FID-TCD gas analysis spectrum. At the same time, the liquid product was centrifuged and separated into layers. After standing, the upper organic phase and the lower aqueous phase were taken and analyzed by gas chromatography. The results are shown in Table 2.

[0044] Application Example 2

[0045] The parameters and steps involved in this application example are the same as those in application example 1. The difference is that the catalyst used is the catalyst provided in Example 2. The results are shown in Table 2.

[0046] Application Example 3

[0047] The parameters and steps involved in this application example are the same as those in application example 1. The difference is that the catalyst used is the catalyst provided in Example 3. The results are shown in Table 2.

[0048] Application Example 4

[0049] The parameters and steps involved in this application example are the same as those in application example 1. The difference is that the catalyst used is the catalyst provided in Example 4. The results are shown in Table 2.

[0050] Application Example 5

[0051] The parameters and steps involved in this application example are the same as those in application example 1. The difference is that the catalyst used is the catalyst provided in Example 5. The results are shown in Table 2.

[0052] Application Example 6

[0053] The parameters and steps involved in this application example are the same as those in application example 1. The difference is that the catalyst used is the catalyst provided in Example 6. The results are shown in Table 2.

[0054] Application Example 7

[0055] The parameters and steps involved in this application example are the same as those in application example 1. The difference is that the catalyst used is the catalyst provided in Example 7. The results are shown in Table 2.

[0056] Application Example 8

[0057] The parameters and steps involved in this application example are the same as those in application example 1. The difference is that the catalyst used is the catalyst provided in Example 8. The results are shown in Table 2.

[0058] Comparative application example 1

[0059] The parameters and steps involved in this comparative application example are the same as those of Application Example 8. The difference is that the catalyst used is the catalyst provided in Comparative Example 1. The results are shown in Table 2.

[0060] Comparative Application Example 2

[0061] The parameters and steps involved in this comparative application example are the same as those in application example 1, except that the catalyst used is the catalyst provided in comparative example 2. The results are shown in Table 2.

[0062] Table 2 Analysis of reaction results of various embodiments and comparative examples

[0063]

[0064] From the data in Table 2, it can be seen that the high-carbon alcohol product in Comparative Example 1 is significantly reduced, indicating that appropriate carbon and nitrogen doping can introduce a base center to promote the coupling of high-carbon aldehydes and ketones to form long-chain alcohols. In Comparative Example 2, C6+ high-carbon alcohols cannot be synthesized, indicating that the long-chain alcohol product requires Cu metal active centers to dehydrogenate ethanol and then achieve CC coupling condensation to grow the carbon chain.

[0065] The present invention adopts Cu / ZrO2@NC catalyst to realize one-step catalytic conversion of ethanol into C6+ higher carbon alcohols. The ethanol conversion rate can reach up to 92.4%, and the C6+ higher carbon alcohol selectivity can reach up to 44.68%, achieving C6 alcohol selectivity greater than C4 alcohol, breaking the traditional carbon number distribution, and taking into account the balance of high ethanol conversion rate, long higher carbon alcohol carbon chain, and high selectivity.

[0066] The above are only preferred specific implementation methods of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed in the present application should be included in the protection scope of the present application; therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher alcohols from ethanol, characterized in that: The steps are as follows: 1) adding copper salt, zirconium salt and polyacrylamide into water, dissolving and mixing, heating and stirring to form a complex homogeneous solution, and drying to obtain a copper-zirconium catalyst precursor; 2) calcining the copper-zirconium catalyst precursor prepared in step 1) under an inert gas atmosphere to obtain a Cu / ZrO2@NC catalyst; The molar ratio of the copper ions in the copper salt, the copper ions in the zirconium salt and the carbon of the polyacrylamide is (0.1-0.5):1:(0.5-2).

2. The method for preparing a Cu / ZrO2@NC catalyst for catalyzing ethanol to synthesize higher alcohols according to claim 1, characterized in that: The copper salt is one or more of copper nitrate, copper chloride and copper acetate.

3. The method for preparing a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher alcohols from ethanol according to claim 1, characterized in that: The zirconium salt is one or more of zirconium nitrate, zirconium citrate and zirconium hydroxide.

4. The method for preparing a Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher alcohols from ethanol according to claim 1, characterized in that: The calcination parameters are: heating rate 5°C / min, temperature 500-600°C, and time 3h.

5. A Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher alcohols from ethanol, characterized in that: The preparation method according to any one of claims 1 to 4.

6. The Cu / ZrO2@NC catalyst for catalyzing the synthesis of higher carbon alcohols from ethanol as claimed in claim 1 is used for catalyzing the synthesis of higher carbon alcohols from ethanol.

7. A method for synthesizing higher alcohols from ethanol, characterized in that: The steps are as follows: 1) 1 ml Cu / ZrO2@NC catalyst and 2 ml quartz sand were loaded into a fixed bed reactor and mixed evenly; the temperature was raised from room temperature to 400 °C at a rate of 5 °C / min under a hydrogen atmosphere and kept at this temperature for 2400 h. -1 Hydrogen gas space velocity 0.1MPa reduction for 2h; 2) Keeping the H2 gas atmosphere unchanged, the pressure was increased to 2.5Mpa, the reaction temperature was 310℃, and the reaction time was 0.6h. -1 Anhydrous ethanol was added to the reactor at a liquid rate of 3600 h. -1 , reaction time 12h; 3) Collect the generated gas and perform detection and analysis by FID-TCD gas analysis spectrum. Meanwhile, centrifuge and separate the liquid phase products, take the upper organic phase and the lower aqueous phase after standing, and perform detection and analysis by gas chromatography.

Citation Information

Patent Citations

  • Catalyst for preparing distillate oil co-production high alcohol with synthesis gas, preparation method and application

    CN102872870A

  • Oxalate hydrogenation catalyst for producing ethanol and preparation method of catalyst

    CN105126845A

  • High-activity Cu / ZrO2@CN catalyst as well as preparation method and application

    CN109759118A

  • Nitrogen-doped carbon-coated nickel catalyst applied to assembling bioethanol to synthesize high-carbon alcohol, and preparation method thereof

    CN113145155A

  • Method for synthesizing higher alcohol through continuous catalytic conversion of ethanol

    CN117645528A